Pengaruh Kompensasi Dan Shift Jam Kerja Terhadap Kepuasan Kerja Pada Badan Penanggulangan Bencana Daerah (BPBD) Kota Bima - Anggi Anggriani; Muhammad Badar (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
Job satisfaction is a psychological aspect that reflects a person's feelings towards his job. Basically job satisfaction is an individual thing because each individual will have a different level of satisfaction according to the values ​​that apply to each individual. Based on the results of observations, there are several problems faced by employees at BPBD including, the compensation provided is not in accordance with the employee's workload and the shift of working hours charged is too burdensome for honorariums. Therefore, the provision of compensation and work shifts are factors that are mentioned as factors that trigger job satisfaction. Compensation for employees who shift working hours provides satisfaction for employees. The purpose of this study was to determine the effect of compensation and shift work hours on job satisfaction. This type of research is associative. The instrument of this research is a questionnaire. The result of this research is that compensation has a partial effect on job satisfaction at the Regional Disaster Management Agency (BPBD). Shift work hours have a partial effect on job satisfaction at the Regional Disaster Management Agency (BPBD). Simultaneously, compensation and shift work hours affect job satisfaction at the Regional Disaster Management Agency (BPBD).